Practices of Primary Schools Cluster Supervision: The Case of Jimma Town Primary Schools in Ethiopia - Tadele, Kasahun; Bekele, Mitiku (European Scientific Journal, ESJ, 2017)
The purpose of the study was to investigate the Practices of Cluster Supervision in Jimma town primary schools. To achieve this purpose, descriptive survey research design was employed as it helps to describe the status of the cluster supervision. Accordingly, 11 primary schools were selected by using stratified sampling technique from five Cluster Resource Centers (CRCs). From the 11 primary schools 126 teachers were selected using simple random sampling technique to represent the population. Moreover, 26 school principals, 5 CRC supervisors, and 1 Education Office Supervision Coordinator were included by purposefully. Data were collected using questionnaires, interview, observation and document analysis. Frequency, percentages, Mann Whitney U Independent Sample Test and Chi-square were used to analyze the quantitative data. The qualitative data was analyzed thematically. Consequently, the obtained results revealed that the CRC supervisors were not effective in promoting teachers professional development and instructional skills. They were not also able to frequently visit schools and classroom for closer support. Even though cluster supervisors support the schools’ management in ensuring good governance and providing timely information, they were not able to adequately enhance the school principals’ planning, decision making and internal management capacity. Moreover, the supervision practice was not successful in creating strong collaboration between all stakeholders. In conclusion, cluster school supervision is highly challenged due to lack of practical competence and adequate preparation of supervisors on one hand and the poor working conditions of supervisors on the other hand. Therefore, it is recommended that Regional Education Bureau and Jimma Town Education Officers work in collaboration with Jimma College of Teacher Education and Jimma University to provide adequate training for cluster supervisors in the town Jimma town supervision coordinator should also work very closely with the cluster supervisors in identifying the important training needs and providing accordingly to improve the quality of supervision that impact positively the quality teaching and learning. Finally, the Jimma Twon Education Office should allocate adequate budget and create conductive working conditions to achieve the objectives of teaching and learning.